2015
DOI: 10.1182/blood-2015-03-635169
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive monitoring of diffuse large B-cell lymphoma by immunoglobulin high-throughput sequencing

Abstract: Key Points• DLBCL can be detected in the blood by immunoglobulin high-throughput sequencing (Ig-HTS) with high specificity.• Although DLBCL can be detected in leukocytes or plasma by Ig-HTS, plasma has greater sensitivity and more accurately reflects disease.Recent studies have shown limited utility of routine surveillance imaging for diffuse large B-cell lymphoma (DLBCL) patients achieving remission. Detection of molecular disease by immunoglobulin high-throughput sequencing (Ig-HTS) from peripheral blood pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
275
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(292 citation statements)
references
References 42 publications
7
275
2
8
Order By: Relevance
“…The 3-years follow-up period showed that total level of ccfDNA at diagnosis, had prognosis value in terms of DFS, since it was shorter in the group of patients that had a ccfDNA concentration over 46 ng/ml [58]. [62]. So far, including this paper, clonotypic sequences identified in ctDNA and CTCs, has to be compared to the sequences found in fresh or frozen tissue samples from the same patient.…”
Section: Non-hodgkin Lymphomas (Nhl)mentioning
confidence: 96%
“…The 3-years follow-up period showed that total level of ccfDNA at diagnosis, had prognosis value in terms of DFS, since it was shorter in the group of patients that had a ccfDNA concentration over 46 ng/ml [58]. [62]. So far, including this paper, clonotypic sequences identified in ctDNA and CTCs, has to be compared to the sequences found in fresh or frozen tissue samples from the same patient.…”
Section: Non-hodgkin Lymphomas (Nhl)mentioning
confidence: 96%
“…Therefore, ctDNA analysis might overcome some limitations of the current MRD approach in NHL. First, it can avoid falsenegative MRD results: as ctDNA gives a better representation of tumor masses (lymph nodes) rather than leukemic disease, ctDNA might help in localized relapses, not detectable either in PB or in BM; in addition, it may extend the application of MRD to non-or less leukemic disorders, such as DLBCL (102,103), primary central nervous system lymphoma (PCNSL) (104), stage I FL or WM (105); finally, it is likely to decrease or avoid invasive diagnostic procedures (BM biopsy or lumbar puncture) to monitor MRD.…”
Section: Future Directions Of Mrd Studies: Novel Tools Tissues and mentioning
confidence: 99%
“…Currently, most clinical laboratories take a targeted gene panel approach instead of performing whole-exome or whole-genome sequencing to identify clonal markers to aid in diagnosis, evaluation of prognosis, choice of molecular targets, and treatment monitoring. [101][102][103][104][105][106] For example, at Emory we are validating and will soon implement a targeted gene panel for myeloid neoplasms. This laboratory-developed NGS test protocol is based on a well-validated research use-only kit that targets 54 genes, including all exons of 15 genes (BCOR, BCORL1, CDKN2A, CEBPA, CUX1, DNMT3A, ETV6, EZH2, IKZF1, KDM6A, PHF6, RAD21, RUNX1, STAG2, and ZRSR2) and hot spot exons/regions of 39 genes (ABL1, ASXL1, ATRX, BRAF, CALR, CBL, CBLB, CBLC, CSF3R, FBXW7, FLT3, GATA1, GATA2, GNAS, HRAS, IDH1, IDH2, JAK2, JAK3, KIT, KMT2A/MLL, KRAS, MPL, MYD88, NOTCH1, NPM1, NRAS, PDGFRA, PTEN, PTPN11, SETBP1, SF3B1, SMC1A, SMC3, SRSF2, TET2, TP53, U2AF1, and WT1).…”
Section: Next-generation Sequencingmentioning
confidence: 99%